Daqing Oil Cluster: From petroleum hub to sustainable future - Zhu, Penglin (International Planning History Society Proceedings, 2018)
Since the mid-20th century, the Chinese government in collaboration with various governmental petroleum authorities, first with the Ministry of Petroleum and later with state-owned companies, has transformed the built environment on multiple levels, creating interrelated infrastructures and production sites, installing refineries and petrochemical industries, constructing dedicated oil ports, building workers’ housing and educational, health or leisure facilities, effectively creating a palimpsestic petroleumscape. The development of Daqing oil field can be the best representor showing the how the Chinese government shaped the built environment and people’s lifestyle. Urban form in Daqing has changed extensively after the Chinese Economic Reform in early-1980s when the national policy shifted to complete and optimize the infrastructure and civic facilities. The recent national policies of the OBOR Initiative, which aims at balancing the economic sustainability and environmental preservation and Revitalizing the Old Industrial Bases in China have helped develop Daqing at the regional scale, Moreover, these national plans aim at balancing two potentially conflicting objectives: economic development and ecological sustainability. This paper explores in which manner the national policies and local spatial plans of Daqing have transform Daqing from the old oil mining district to the domestic oil hub, then to a sustainable oil cluster.